SIGHT SINGING SEBAGAI STRATEGI PEMBELAJARAN INSTRUMEN PIANO DI PRODI PENDIDIKAN MUSIK ISI YOGYAKARTA - Suryati, Suryati; Widodo, Tri Wahyu (Resital: Jurnal Seni Pertunjukan, 2020)
Sight Singing is the ability to read the notation and immediately sing the tune in accordance with the melody on the sheet music. Sight Singing is the activity of singing with solmisasi or movabel "do". This study aims to improve the ability to read beam notation in learning mandatory piano instruments using the Sight Singing approach. The Mandatory Piano Instrument course is one of the practical courses that must be taken by all Music Education Study Program students, ISI Yogyakarta. Not all new students in Music Education Study Program can read the beam notation, so this Piano Compulsory Instrument course course is always feared by students who have not read fluent notation. Sight singing as a strategy to enhance the learning of Piano Mandatory Instruments. This research is focused on the application of Sight singing in learning Mandatory Piano Instruments in Music Education Study Program. This research uses Classroom Action Research which can be categorized as a qualitative-experimental research by applying the Sight singing method. The results of this study are the learning process of the Mandatory Piano Instrument with the application of the Sight singing method more effectively to improve the ability to learn to read notation while playing the Piano Instrument, and students can be more expressing, impressed singing by accompanying themselves.